Предмет: Математика, автор: nznns

Помогите решить это уравнение!

Приложения:

sydzyme: Невидно что делать

Ответы

Автор ответа: SvePap26
1
(3 \frac{9}{16}  - y) + 4 \frac{9}{16}  = 5 \frac{7}{16}
3 \frac{9}{16}  - y = 5 \frac{7}{16} - 4 \frac{9}{16}
5 \frac{7}{16}  - 4 \frac{9}{16}  = 4 \frac{23}{16}  - 4  \frac{9}{16}  =  \frac{14}{16}
3 \frac{9}{16}  - y =  \frac{14}{16}
y = 3  \frac{9}{16}  - \frac{14}{16}  = 2 \frac{25}{16}  -  \frac{14}{16}  = 2 \frac{11}{16}
y = 2 \frac{11}{16}
Вроде так




nznns: Спасибо
Похожие вопросы